PENINGKATAN HASIL BELAJAR MENULIS PANTUN PADA SISWA KELAS IV SDN 037 SABANG BANDUNG MELALUI MODEL THINK TALK WRITE (TTW) - K, Triwahjuni; Rahayu, Galih Dani Septiyan (COLLASE (Creative of Learning Students Elementary Education), 2021)
Problems in making rhymes sometimes occur in several public elementary schools in Bandung in the academic year 2019/2020. Based on observations and interviews with teachers conducted by researchers in fourth-grade students SDN 037 Negeri Sabang found that there is a low motivation to learn students seen from the inactivity of students asking questions when given the opportunity to ask questions by the teacher; Researchers set problem-solving with the TTW learning model to solve problems in the learning process of writing rhymes for fourth-grade students of SDN 037 Sabang. The purpose of this research is by choosing the TTW model because the TTW model helps students to understand the subject matter through direct learning using the TTW model so that students are able to carry out the stages of thinking and noting the unknowns correctly, discussing in groups, and writing rhymes. The research method used in this research is a descriptive qualitative method. The results of this study in the form of the application of the Think Talk Write (TTW) learning model helped students in fourth-grade students in SDN 037 Sabang Bandung in completing their poetry writing assignments and helped students in fourth-grade students in SDN 037 Sabang Bandung in thinking (think) and communicating with friends (talk ), teachers, and even with themselves in producing work in the form of poetry writing skills (write).